EU Clinical Trials Regulation 2014: Fetter or facilitator?. (June 2018) - Cave, Emma
European Union (EU) Clinical Trials Regulation 536/2014, expected to come into force in 2019, provides for a streamlined single EU application for cross-border clinical trials and enhanced transparency of results. The status of the Regulation in post-Brexit UK is uncertain. Matters of regulatory alignment will be covered by agreements on the future EU-UK relationship. In the short term, implementation of the Regulation in the United Kingdom depends on the Brexit model and timing of the Regulation's implementation. The EU (Withdrawal) Act will convert EU law into UK law, including the vast array of EU life sciences regulation. However, the Regulation is likely to be implemented after the United Kingdom leaves the EU, but within the transition period. If the United Kingdom is not part of the legal framework governing clinical trials in the EU, then the United Kingdom will still need to comply with the global framework set out in the International Council on Harmonisation if it wants to be part of trials of medicinal products for which marketing authorization will be sought for licensing in the European Economic Area. This article extols the virtues of harmonization with the EU and attempts to counter some of the media focus on the advantages of a deregulated bespoke approach.